Odontogenic Keratocyst in Mandibular Premolar Region- A Case Report - Aishwarya. S, Aishwarya. S; Krishnan, Bala (Journal of Neonatal Surgery, 2025)
A growing odontogenic cyst known as an odontogenic keratocyst is frequently detected in the early stages of routine radiography. This means that the dentist is now more responsible for diagnosing the patient accurately and should treat the maxillomandibular complex as a whole rather than just the individual teeth. Because of this, the dentist is now more accountable for making the correct diagnosis and should focus on the entire maxillomandibular complex rather than just the teeth. Because of its aggressive nature and greater propensity for recurrence, OKC has a peculiar feature. OKC may sometimes left undiagnosed in many cases as it does not show any evident swelling in the affected region as it’s tendency of expansion is generally antero posterior direction instead of bucco-lingual expansion. It is usually identified as an incidental finding in dental radiographic images. A case of a Keratocystic Odontogenic Tumor of Unknown Origin in the Canine Premolar Region of the Right Mandible is presented in this article